2004
DOI: 10.1080/0266736042000251826
|View full text |Cite
|
Sign up to set email alerts
|

‘I Am the Hate that Dare Not Speak its Name’: Dealing with homophobia in secondary schools

Abstract: This paper describes the outcomes of a small-scale project involving 19 secondary schools. The project investigated how effectively issues of homophobic bullying and sexualities were addressed through secondary schools' formal policies and areas of the curriculum. Outcomes indicate that sexual orientation was mentioned in two-thirds of Equal Opportunities policies but was not mentioned speci®cally in any Anti-Bullying policies. Staff highlighted the need for training in issues surrounding sexualities, homophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 3 publications
(2 reference statements)
2
13
1
10
Order By: Relevance
“…Victims of bullying are often portrayed as loners (Adams, Cox, & Dunstan, 2004;Dupper & Meyer-Adams, 2002;Smith, Talamelli, Cowie, Naylor, & Chauhan, 2004). This was not found in this study.…”
Section: Friendship In Schooling Spacescontrasting
confidence: 75%
See 1 more Smart Citation
“…Victims of bullying are often portrayed as loners (Adams, Cox, & Dunstan, 2004;Dupper & Meyer-Adams, 2002;Smith, Talamelli, Cowie, Naylor, & Chauhan, 2004). This was not found in this study.…”
Section: Friendship In Schooling Spacescontrasting
confidence: 75%
“…According to recent studies (Chambers, Ticknell, & van Loost, 2004;Adams, Cox, & Dunstan, 2004) although teachers identified homophobic bullying as a serious problem (albeit addressed inadequately), it is not always taken as seriously as other forms of bullying by teachers as it is often seen as a "natural" reaction of young men.…”
Section: Journal Of Lgbt Youthmentioning
confidence: 96%
“…Este resultado é consonante com a literatura, que alerta para o comprometimento do desenvolvimento e da saúde global das vítimas (Adams et al, 2004;Meyer, 2010;Swearer et al, 2008;Zinner et al, 2012), para a angústia psicológica (Swearer et al, 2008), para os sintomas de depressão, ansiedade, stresse e para a diminuição do vínculo à escola (Poteat & Espelage, 2007).…”
Section: Discussionunclassified
“…Ao nível do género (Poteat & Espelage, 2007) mostram que, para os rapazes, ser vítima de bullying homofóbico pode predizer fortes sintomas de depressão, ansiedade, stresse e diminuição do sentimento de ligação à instituição escolar, não sendo uma situação tão ameaçadora para o self nas raparigas. Relativamente às vítimas gays e lésbicas, observou-se que 40% das vítimas tentaram o suicídio (Adams, Cox, & Dunstan, 2004).…”
unclassified
“…This diversion from social bias was addressed partially by Adams, Cox, and Dunstan (2004) suggesting the proactive involvement of EPs to combat implicit bullying. More importantly, Robertson and Monsen (2001) suggested that EPs, as members of society, may also hold cultural bias towards heterosexism and suggested accountability for EPs in acting in this area at different systems levels.…”
Section: Sexuality Diversity and Educational Psychologistsmentioning
confidence: 99%